2011
DOI: 10.1111/j.1443-1661.2011.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Lesions Detected With Wireless Capsule Endoscopy in Patients With Active Ulcerative Colitis and With Post-Proctocolectomy

Abstract: Background: Although rare, duodenal lesions have been reported in association with ulcerative colitis (UC); however, there have been very few reports on small bowel lesions, and many aspects of their pathology and frequency remain unknown. This study determined whether small bowel lesions are present in UC by using wireless capsule endoscopy (WCE). Patients and Methods: WCE was performed on 20 patients with active UC and 10 who had undergone proctocolectomy. Results: Small bowel lesions (e.g. edema or ulcers) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
(40 reference statements)
0
17
1
Order By: Relevance
“…This study investigated clinical features in UC patients with and without small bowel lesions, but found no differences in disease type or disease activity. This result differed from a previous study describing higher frequencies of small bowel lesions in active UC patients with extensive type UC [13]. However, in our study, endoscopic activity was significantly higher in the UC subgroup with small bowel lesions than in the subgroup without such lesions.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This study investigated clinical features in UC patients with and without small bowel lesions, but found no differences in disease type or disease activity. This result differed from a previous study describing higher frequencies of small bowel lesions in active UC patients with extensive type UC [13]. However, in our study, endoscopic activity was significantly higher in the UC subgroup with small bowel lesions than in the subgroup without such lesions.…”
Section: Discussioncontrasting
confidence: 56%
“…The presence of gastroduodenal lesions [5-10] and small bowel lesions [11-15] in UC has been reported in recent years, with an incidence of 4.7–7.6% [8, 9] for gastroduodenal lesions and 36–57% [13, 14] for small bowel lesions. Our study similarly found an incidence of 27.8% for small bowel lesions in UC, lending further support to the idea that such lesions are not uncommon in UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with CD, the role of CE in UC patients is limited. Recent studies indicated that small intestinal lesions were detected using CE in patients with UC . However, the clinical significance of these intestinal lesions in UC patients remains to be defined.…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…Recent studies indicated that small intestinal lesions were detected using CE in patients with UC. 16,17 However, the clinical significance of these intestinal lesions in UC patients remains to be defined. Recently, our group established the applicability of colon CE in patients with UC.…”
Section: Capsule Endoscopymentioning
confidence: 99%